First‐line crizotinib versus platinum‐pemetrexed chemotherapy in patients with advanced ROS1‐rearranged non‐small‐cell lung cancer. (13th March 2020) - Shen, Lan; Qiang, Tan; Li, Ziming; Ding, Ding; Yu, Yongfeng; Lu, Shun
Abstract: Objectives: Food and Drug Administration (FDA) approved crizotinib for advanced ROS1‐rearranged ( ROS1+ ) non‐small‐cell lung cancer (NSCLC) patients due to a single‐arm study PROFILE 1001. However, there is no direct comparison between crizotinib and platinum‐pemetrexed chemotherapy. Materials and methods: Clinical data of advanced ROS1+ NSCLC patients treated with first‐line crizotinib or platinum‐pemetrexed chemotherapy between August 2010 and December 2017 were analyzed. Results: Seventy‐seven patients were eligible, including 30 (39.0%) in the crizotinib group and 47 (61.0%) in the platinum‐pemetrexed chemotherapy group. The median follow‐up was 28.1 months (95% confidence interval [CI]: 19.2‐39.0). The objective response rate (ORR) of crizotinib (86.7%, 95% CI: 73.3‐96.7) was higher than that of platinum‐pemetrexed chemotherapy (44.7%, 95% CI: 29.8‐57.4, P  < .001). The disease control rate (DCR) was 96.7% (95% CI: 90.0‐100) in the crizotinib group and 85.1% (95% CI: 74.5‐95.7) in the chemotherapy group ( P  = .140). Significantly longer progression‐free survival (PFS) was observed in the patients treated with crizotinib (18.4 months, 95% CI: 6.4‐30.3) versus platinum‐pemetrexed chemotherapy (8.6 months, 95% CI: 6.9‐10.3, P  < .001). Overall survival (OS) was also compared between the two groups and no significant difference was seen (Not reach vs 28.4 months [95% CI: 20.7‐36.0], P  = .176). Notably, a total of 37 patients have treatment crossover after the failure of first‐line treatment. Among those patients, difference in OS was not statistically significant between seven patients who have given first‐line crizotinib (38.6 months, 95% CI: 0‐81.0) and 30 patients who have given platinum‐pemetrexed chemotherapy initially (32.8 months, 95% CI: 11.9‐53.8, P  = .805). Conclusions: Our results suggested that first‐line crizotinib had higher ORR and longer PFS than platinum‐pemetrexed chemotherapy in patients with advanced ROS1+ NSCLC, but the differences were not observed for OS. Abstract : This is the first study to compare crizotinib with chemotherapy in ROS1+NSCLC. Crizotinib was superior to platinum‐pemetrexed chemotherapy as an initial treatment.